Post-September 11 discourse : the case of Iran in The New York Times. - Jahedi, Maryam; Abdullah, Faiz Sathi (Canadian Center of Science and Education, 2012)
This study examined how discursive strategies and related linguistic devices were employed by The New York Times (TNYT) to portray Iran after the terrorist attacks in the U.S. on September 11, 2001, and how the media representation may have contributed to negative and/or positive outcomes in terms of geopolitical relations. The study also investigated how sociopolitical assumptions were manifest in producing news about Iran and how the news discourse continued to shape the power relations between the nation and the U.S. in particular, and the world at large. Using Critical Discourse Analysis (CDA) as a multidisciplinary approach, the analysis focused on 171 front-page TNYT news articles from 2001 until 2009. Analysis of the discursive strategies and linguistic means revealed that the news media depicted an overall negative picture of Iran after the September 11 or “9/11” attacks. The effect of this rather stereotypical construction of Iran in TNYT was that of the negative Other, a nation of people that formed part of George W. Bush’s contentious “axis of evil” thesis–malevolent, untrustworthy, violent, and a threat to world peace.